Simulation of cyclone separator for particulate removal from syngas - Monir, Minhaj Uddin; Azrina, Abd Aziz; Yousuf, Abu; Hossain, Jafar; Habib, Ahosan; Techato, Kuaanan; Phoungthong, Khamphe (Elsevier, 2022)
This chapter deals with the simulation of cyclone separator for particulate removal from syngas. One of the most difficult issues of the gasification process is the presence of particles in syngas, which requires expert attention: these solid particles should be eliminated by utilizing solid separators. A cyclone separator is a particle separation device that allows solid effluent and dust particles from the reaction to drop down the cyclone's conic section. The operating principles have introduced several kinds of technology to remove particles. This chapter begins by presenting syngas contaminants and technology for particle removal from syngas. This chapter discussed the significance and processes of simulation work. Besides, simulation parameters and process optimization are obtained. Therefore, outcome of this chapter will provide future study directions for parameter optimization through simulation work for particle separation from syngas.